‘We no longer love you, but we don’t want to leave you’: the Eurozone crisis and popular Euroscepticism in Greece - Clements, Ben; Nanou, Kyriaki; Verney, Susannah (Taylor & Francis, 2014)
This article analyses whether and how public opinion towards the European Union (EU) in Greece has changed in the context of the current Eurozone crisis. It provides the first detailed treatment of how the crisis has affected citizens’ views in a traditionally pro-European member state. It examines whether public opinion has become more Eurosceptic and which societal groups have changed their views and in what direction. It uses data from Eurobarometer surveys conducted before and during the current crisis. Unsurprisingly, the findings show that negative sentiment towards the EU has increased across all social groups in recent years. However, we find a paradox of a decline in general support for the EU and an increase in support for the Euro. In a country seen as traditionally pro-European, Greek public opinion has fallen out of love with the EU, but it clearly does not want to leave the Eurozone or renounce membership altogether.